Big Greek Idea Series : Ephesians : an exegetical guide for preaching and teaching - Simpson, Benjamin I.; Bateman, Herbert W., 1955- (Grand Rapids, MI. Kregel Academic, 2020)
Big Greek Idea provides all the relevant information from the Greek text for preaching and teaching the New Testament. Each New Testament book is divided into units of thought, revealing a big Greek idea (the author's main idea in the passage), and individual clauses are displayed visually to illustrate their relationships, portraying the biblical author's logical flow. Greek clauses are accompanied by an original English translation. --
Includes bibliographical references (pages 398-403) and index
Keywords: Bible. -- Commentaries; Bible. -- Study and teaching